Interrelated transformative process dynamics in the face of resource nexus challenges: an invitation towards cross case analysis - Heila Lotz-Sisitka; Claudia Pahl-Wostl; Richard Meissner; Geeske Scholz; Jessica Cockburn; Experencia Madalitso Jalasi; Sabine Stuart-Hill; Carolyn (Tally) Palmer (Ecosystems and People)
The need for more attention to the social and human dimensions in global change sciences and natural resources management requires in-depth understandings of transformative approaches and processes. More inclusive and systemic approaches are needed that embrace complexity and support transformative learning, shifts in power relations, collective and relational agency and structural transformations for adaptive and innovative governance. Scientific understanding of how such change can be brought about is still limited. In this paper, which sets the scene for this Special Issue, we develop a conceptual framework for analyzing transformative processes across a range of diverse cases. Aspects of the conceptual framework are applied, tested and elaborated in three following papers in the Special Issue, deepening understanding of how transformative change in complex social-ecological systems may originate at nexus boundary zones such as that portrayed by the water-food-energy nexus. Specifically, the paper conceptually elaborates four iteratively related dynamics of transformative learning, transforming power relations, transformative agency and transforming structures which intersect in transformation processes. The perspectives offer tools for cross case analysis in the longer term, but also tools for supporting co-engaged, generative research processes.